PENGEMBANGAN DESAIN BAHAN AJAR BERMUATAN 6C PADA MATERI TRIGONOMETRI KELAS X SMKN 2 PACITAN - Setiyowati, Ayu; Apriyani, Dwi Cahyani Nur; Qudsiyah, Khoirul (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2023)
The research aims to develop LKPD containing 6C and to know the quality of the LKPD that has been developed. This research is a development research (R&D) with a 4-D development model namely Define, Design, Develop, and Disseminate. The results showed that the developed LKPD had good quality based on the results of expert validation and development trials. Expert validation was carried out with 3 validators namely material expert validation, design expert validation, and linguist validation with successive percentage scores of 85%, 84%, 96% with very good criteria. Development trials were carried out 2 times with a percentage score of 77% and 83% with good and very good criteria.